2022
DOI: 10.1101/2022.07.27.501663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptome analysis reveals heterogeneity and a dynamic regenerative response of quiescent radial glia in adult zebrafish brain

Abstract: In zebrafish telencephalon, radial glial cells (RGs) show a remarkable ability to regenerate damaged neural tissue by re-initiating cell proliferation to produce neural precursors to rebuild the lost neural circuit. However, it is not fully understood how RGs respond to brain damage to initiate this regenerative response. Here we applied single-cell transcriptomics to RGs in adult zebrafish telencephalon and identified five RG subtypes, which are classified into four quiescent RGs (qRGs) and one proliferating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…The initial GC-induced increase in cell proliferation observed here might be in part mediated by mechanisms akin to those observed during brain injury, whereby formerly quiescent radial glia enter the cell cycle in response to trauma 26,51 . In the published literature, there are very few previous studies of effects of GC on cell proliferation across development.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The initial GC-induced increase in cell proliferation observed here might be in part mediated by mechanisms akin to those observed during brain injury, whereby formerly quiescent radial glia enter the cell cycle in response to trauma 26,51 . In the published literature, there are very few previous studies of effects of GC on cell proliferation across development.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed the concept of GC-inducible stem cells is not novel 47,48 , and there are many reports of a GC-induced increase in cell proliferation of various cell types including NSPCs 49,50,51,52 . The initial GC-induced increase in cell proliferation observed here might be in part mediated by mechanisms akin to those observed during brain injury, whereby formerly quiescent radial glia enter the cell cycle in response to trauma 28,53 . In the published literature, there are very few previous studies of effects of GC on cell proliferation across development.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This aligns with the concept of GC-inducible stem cells 31,32 . Previous studies have demonstrated GC-induced proliferation in various contexts [33][34][35][36] , resembling mechanisms observed during brain injury, where quiescent radial glia enter the cell cycle in response to trauma 29,37 . Few studies have explored the developmental impact of GC on cell proliferation.…”
Section: Discussionmentioning
confidence: 66%
“…Whilst rx3 appeared to be co-expressed with Pcna in proliferating radial glia, we also analysed Blbp (brain lipid binding protein, fabp7a) localisation, which is known to be expressed in predominantly quiescent radial glia in the zebrafish brain 29 . Consistent with this, we observed strong expression of Blbp in cells lining the third ventricle in the Pcna-negative rostral domains of the hypothalamus, whilst some Blbp signal was also observed in Pcna-positive cells of the lateral recess (Fig.…”
Section: Precocious Hypothalamic Development Following Elevated Gcmentioning
confidence: 99%